(untitled) (Ciudades, 2017)
Bussy Saint Georges is one of the twelve municipalities making up the « secteur 3 » of the new town of Marne-la-Vallée. Its recent history can be considered emblematic of how the State great project of creating new centralities in Ile-de-France (villes nouvelles) had to face the resistance of territories. However Bussy hasn’t been characterized by the ultraconservative policy, typical of the neighboring municipalities. It represents instead the story of how local councilors, by using demagogically the theme of the « local » embodied in a « neo traditional » architectural style, achieved to impose to a central government. The original concept of « new centralities » of the State project, reduced to an image of itself, has been perverted into a series of « microcentralities » , disconnected from any regional or metropolitan consistency.